PENGEMBANGAN LKPD BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR GEOMETRIK MURID KELAS V SEKOLAH DASAR - Kurnia Nabilah Far'hah; Puri Pramudiani (Universitas Muhammadiyah Metro, 2026)
This study focused on the design and implementation of an Augmented Reality (AR)-integrated student worksheet (LKPD) aimed at improving fifth-grade students’ geometric thinking skills, particularly in learning about cubes and rectangular prisms. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were 29 fifth-grade students from a public elementary school in Bekasi, Indonesia. Data were collected through observations, interviews, validation sheets, and pretest–posttest instruments. The validation results showed that the material aspect obtained 90% in the very valid category, the media aspect obtained 76% in the valid category, and the language aspect obtained 75% in the valid category. The results also indicated a significant improvement in students’ geometric thinking skills, with the mean score increasing from 58.86 on the pretest to 86.00 on the posttest. Furthermore, the Wilcoxon Signed Rank Test showed a significance value of p < 0.05, indicating a statistically significant difference between pretest and posttest scores. The effect size result (r ≈ 0.88) was categorized as very large, demonstrating a strong impact of the developed learning media on students’ geometric thinking skills. These findings indicate that the AR-based student worksheet is valid and effective in improving students’ geometric thinking skills. Therefore, the AR-based woorksheet can serve as an innovative learning medium for supporting mathematics learning in elementary schools.